Meeting 24‐h movement guidelines: Prevalence, correlates, and associations with socioemotional behavior in Spanish minors. (9th February 2022) - López‐Gil, José Francisco; Roman‐Viñas, Blanca; Aznar, Susana; Tremblay, Mark S.
Abstract : The aims of this study were to determine for the first time the prevalence of a national sample of Spanish minors meeting the 24‐h movement guidelines; to determine their correlates; and to examine their associations with socioemotional behavioral problems. Cross‐sectional data from the Spanish National Health Survey (2017) were analyzed for this study. A total of 3772 Spanish minors were included. Physical activity was parent‐reported by a modified short version of the International Physical Activity Questionnaire, which included a single question related to the participation in physical activity in free time. Recreational screen time was parent‐reported by asking respondents for weekdays and weekends independently: "How much time does your child typically spend in front of a screen, including a computer, tablet, television, video, video game, or cell phone screen?". Sleep duration was parent‐reported by the following question: "Can you tell me approximately how many hours your child usually sleeps daily?". The Strengths and Difficulties Questionnaire was applied for the evaluation of socioemotional behavioral problems. The prevalence of meeting of all the three guidelines was 13.5%. Compared to meeting all guidelines, higher odds of socioemotional behavioral problems were found in participants meeting two guidelines (OR = 1.42; CI95%, 1.10–1.83), one guideline (OR = 1.50; 95%CI, 1.14–1.96), or none of the guidelines (OR = 1.92; 95%CI, 1.30–2.83). Our study demonstrated that the proportion of Spanish minors who meet with all the 24‐h movement guidelines is low. Furthermore, it could be relevant to the promotion of the 24‐h movement guidelines to prevent the risk of socioemotional behavioral problems.